Mechanical behavior of rock mass under simulated materials shear testing - Xing-Chao Lin; Gui-Na Zhu; Xing-Song Sun (Građevinar)
In this paper, the influence of joint distribution on the deformation and strength characteristics of rock mass is studied through direct shear tests of five typical distribution types of simulated materials including two joints. The spatial distribution pattern of joints determines the deformation and failure process and the final shape of rock mass, which is mainly manifested as lap failure between joints. By comparing the 25 stress-strain curves obtained from the test, the stress-strain curves are classified into five types. With the increase of the normal stress, the composite shear type gradually transforms to the shear type, and the shear type gradually transforms to the yield type. The joint distribution pattern has a great influence on the shear strength and the maximum difference is 64 %.